CASE REPORT: PHARINGEAL TUBERCULOSIS WITH MILLIARY TUBERCULOSIS - Desvita Sari; Mujahidah; Subakir; Maria Estela Carolina (FAKULTAS KEDOKTERAN DAN ILMU KESEHATAN UNIVERSITAS JAMBI, 2023)
Background: Tuberculosis (TB) based on its manifestations is divided into two, pulmonary and extra pulmonary. Extrapulmonary TB can be miliary TB and pharyngeal TB. Miliary TB is spread by hematogenous spread to several organs. The diagnosis of extrapulmonary TB takes a long time, an accurate examination can determine extrapulmonary TB infection. Case Presentation: A 47-year-old man complained of recurrent pharyngitis and with symptoms of the respiratory system. Physical examination revealed white granulomatous lesions of the pharyngeal mucosa. The results of the tissue biopsy were performed with Ziehl Neelsen staining. The chest x-ray showed miliary tuberculosis. Diagnostic confirmation using sputum and tissue culture on Lowenstein Jensen medium, MPT64, and niacin paper strip test. Gene Xpert results detected Mycobacterium TB and Rifampicin resistance. Antituberculosis is given for four months. Conclusion: Physical examination of the throat revealed granulomatous inflammation and chest X-ray revealed miliary tuberculosis. The results of sputum and tissue culture on Lowenstein Jensen medium, MPT64, and paper strip test for niacin showed positive TB. Keywords: Pharyngeal tuberculosis, miliary tuberculosis, extrapulmonary tuberculosis.